The Comparison of Conversational Features Used by Joe Biden and Donald Trump in Political Debate - Lina Shofiah; Hendi Pratama; Henrikus Joko Yulianto (Universitas Negeri Semarang, 2023)
Conversation analysis is used to identify the use of features in an interaction by considering the institutional settings or situation. Here, political situation is used because of the condition of controlled situation must be different. This study aimed to compare the conversational features used by Joe Biden and Donald Trump in the final presidential election debate of America in 2020. This was a qualitative study using the conversational analysis approach proposed by Schegloff (1974). The data were analyzed based on the conversational features used including turn-taking strategies, adjacency pairs, and repairs. The results found there were some similarities and differences of conversational features used by both candidates. The similarities showed both speakers preferred to use most of all turn-taking strategies, types of first and second-pair parts, and repair strategies. Besides, the differences were found in the number of conversational features used. Donald Trump tent to use more features since he used more turn-taking strategy to take the turn during the debate. In sum, in political setting, people tend to take more turn to share their idea and respond the other. It affects the use of another conversational features including the frequency of using them. Furthermore, the result of comparing using three features in a political situation becomes the novelty of this research since this setting is a rare topic in conversation analysis. This result is also contributed on enriching references of future research using conversation analysis specifically in a political setting.